ANNUAL FACULTY WORK ASSESSMENT BY USING THE INDEX SYSTEM - Konstantin V. Rochev (Высшее образование в России)
Abstract. The article presents brief excerpts from the annual report of the supervisor of the evaluation system of the faculty activities. The author dwells on the description of the gradual continuous improvement of the evaluation system of teachers, the data collection process and summarized results of the teaching staff work at Ukhta State Technical University.